2011
DOI: 10.1038/ijir.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and cardiovascular disease risk differences for erectile dysfunction patients by three metabolic syndrome definitions

Abstract: There is growing evidence of a link between ED, metabolic syndrome (MS) and cardiovascular disease (CVD). The study was to explore the prevalence of MS using three different definitions (World Health Organization (WHO), International Diabetes Foundation (IDF) and Adult Treatment Panel III (ATP III)), and to compare the association of CVD in ED outpatients using these definitions. This study enrolled 254 participants with a mean age of 55.3±0.9 years (range, 21 to 81 years) with ED as diagnosed by International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
3
1
1
Order By: Relevance
“…Data from a Korean population showed the prevalence of MS for women was 26.6% according to the IDF and 31.9% according to the ATPIII-modified [24]. In a recent study in Taiwan, the prevalence of MS in the IDF and ATPIII-modified was 34.3% and 36.6% [7]. The prevalence of these two studies was higher than in our study.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Data from a Korean population showed the prevalence of MS for women was 26.6% according to the IDF and 31.9% according to the ATPIII-modified [24]. In a recent study in Taiwan, the prevalence of MS in the IDF and ATPIII-modified was 34.3% and 36.6% [7]. The prevalence of these two studies was higher than in our study.…”
Section: Discussioncontrasting
confidence: 78%
“…Recent reports suggest that MS criteria are met by approximately 1 in 3 adults [7], [8]. MS not only increases cardiovascular morbidity and mortality but also increases the risk of developing diabetes because its components represent major risk factors for impaired glucose metabolism [9].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with metabolic syndrome are five times more susceptible to chronic diseases [3][4][5][6] and becoming an important cause of morbidity and mortality in Africa. Pieces of evidences suggested that contributing factors were rapid demographic transition, changing behaviors, and lifestyles [2][3][4][5]. The high MetS prevalence was observed in Africa ranged from 17-25% [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, in Sub-Saharan Africa (SSA) its prevalence will be 59% to 179% in 2030 [2][3][4][5]. Even though most of the studies on MetS were conducted in North America, Europe, and Asia [12][13][14], its impact was high in sub-Saharan African; like Kenya (25.6%), and Tanzania (38%) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, a hipertensão arterial está frequentemente associada a gênese ou progressão da DE (Muller e Mulhall, 2006;Shabsigh et al, 2008;Chang et al, 2011).…”
unclassified